An injection and mixing element for delivery and monitoring of inhaled nitric oxide. Issue 1 (December 2016) - Martin, Andrew; Jackson, Chris; Fromont, Samuel; Pont, Chloe; Katz, Ira; Caillobotte, Georges
Abstract Background Inhaled nitric oxide (NO) is a selective pulmonary vasodilator used primarily in the critical care setting for patients concurrently supported by invasive or noninvasive positive pressure ventilation. NO delivery devices interface with ventilator breathing circuits to inject NO in proportion with the flow of air/oxygen through the circuit, in order to maintain a constant, target concentration of inhaled NO. Methods In the present article, a NO injection and mixing element is presented. The device borrows from the design of static elements to promote rapid mixing of injected NO-containing gas with breathing circuit gases. Bench experiments are reported to demonstrate the improved mixing afforded by the injection and mixing element, as compared with conventional breathing circuit adapters, for NO injection into breathing circuits. Computational fluid dynamics simulations are also presented to illustrate mixing patterns and nitrogen dioxide production within the element. Results Over the range of air flow rates and target NO concentrations investigated, mixing length, defined as the downstream distance required for NO concentration to reach within ±5 % of the target concentration, was as high as 47 cm for the conventional breathing circuit adapters, but did not exceed 7.8 cm for the injection and mixing element. Conclusion The injection and mixing element has potential to improve ease of use, compatibility and safety of inhaled NO administration with mechanical ventilators and gas delivery devices.